Komposisi Jenis dan kandungan Karbon Ekosistem Mangrove di Pantai Hubat Kabupaten Sinjai: Species Composition and Carbon Stock of Mangrove Ecosystem in Hubat Beach, Sinjai Regency, Indonesia - Irfan Fauzi; Ridha Alamsyah; Andi Liswahyunih; Andi Tenriawaruwaty (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
The Carbon Content of Mangrove Stands Hubat Beach Sinjai Regency. In the fight against the effects of global warming, mangrove forests are crucial. Mangrove have the capacity to permanently store and absorb carbon from plants. It takes work to learn about and comprehend the capacity of mangrove plants to store and absorb carbon because each mangrove areas contribution to carbon absorption differs. This research was conducted at Hubat Beach, Sanjai Village, East Sinjai Sub-District, Sinjai Regency. Sample measurements were carried out in 8 observation plots spread throughout the mangrove forest. The measured parameters of density, species closure, importance value index and stem diameter. Meanwhile, to determine the carbon content and absorption capacity, the biomass of existing mangrove stands must first be calculated. The research results showed that there were three types of mangroves including Rhizopora mucronata, Sonneratia alba, Avicennia marina. Rhizopora mucronata dominates with a density of 4,230 trees/ha. The diameter of the stem is very small, namely an average of 8.53 cm. The biomass of the Rhizopora mucronata species was obtained on average 105,644 tonnes/ha, carbon content 49,653 tonnes/ha and carbon uptake 182,225 tonnes/ha. Sonneratia alba has a density of 130 trees/h, an average trunk diameter of 22.21 cm. Biomass is 32,484 tonnes/ha with a carbon content of 15,267 tonnes/ha and carbon uptake of 56,032 tonnes/ha. The density of Avicennia marina is 150 trees/ha with an average trunk diameter of 12.64 cm. The carbon content was 1,734 tons/ha and carbon uptake reached 7,536 tons/ha, the biomass obtained was 3,689 tons/ha